Application of The SCM Concept in Maintaining Smoothness of Cabinet Production - Chalista Alfina; Maulana Dwi Sena; Sudarmin (ITEJ (Information Technology Engineering Journals), 2026)
This study examines the application of Supply Chain Management (SCM) concepts in maintaining the smoothness and efficiency of cabinet production processes. In highly competitive manufacturing environments, production continuity is crucial to meeting customer demand and ensuring operational effectiveness. This research adopts a qualitative descriptive approach, collecting data through observations, interviews, and documentation within a cabinet manufacturing company. The findings reveal that the implementation of SCM practices such as supplier integration, inventory control, demand forecasting, and coordinated production planning significantly enhances material availability, reduces production delays, and minimizes operational disruptions. Furthermore, effective collaboration among supply chain actors improves communication flow and responsiveness to market changes. The study concludes that adopting SCM concepts not only ensures smoother production processes but also contributes to cost efficiency and improved customer satisfaction. These results highlight the strategic importance of SCM in strengthening manufacturing performance and sustaining business competitiveness in dynamic industrial environments..